Effectiveness of Poster and Video Health Promotion Media on Smoking Awareness in Secondary Schools in Depok City, West Java - Saputra, Dwi Arwandi Yogi; Harjono, Yanti; Savitri, Pritha Maya; Fauzan, Ahmad; Alhafiz, Abisha Rakadynan (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract Background: Smoking is hazardous for the health of individuals and those around them. This study aims to identify effective health promotion media to increase awareness of the dangers of smoking in high schools as an effort to enhance understanding of the danger of smoking.Methods: Cross sectional study was conducted on 69 grade X students in 2 high schools in Depok City selected by total sampling. Research variables in the form of health promotion media posters and videos on awareness of the dangers of smoking. Primary data were collected directly using a standardised questionnaire that had been tested for validity and reliability. Data were tested using the Wilcoxon test.Results: There was a significant difference between health promotion posters decreased by 9 people and increased by 12 people. This difference was not significant (p>0.05) with a p-value of 0.972. Poster-based health prevention measures have no effect on smoking knowledge. Health promotion video media has a p-value of 0.000 (p < 0.05) with a decrease of 2 people and an increase of 24 people.Conclusion: The use of video health promotion media and poster media improved adolescents' understanding of the dangers of smoking. Video media is more effective than posters in providing information to high school students in Depok, West Java. A suggestion for the government is to use health promotion videos as an innovative strategy to prevent adolescent smoking. Health promotion media should be shared on popular social media platforms such as YouTube, Instagram, and TikTok, which are frequently used by students.Keywords: Health promotion, Media, Poster, Smoking, Video Abstrak Latar belakang: Perilaku merokok sangat berbahaya bagi kesehatan individu yang merokok dan orang-orang sekitar. Penelitian ini bertujuan untuk mengetahui media promosi kesehatan yang efektif untuk meningkatkan akan bahaya merokok pada sekolah menengah atas dalam upaya peningkatan kesadaran bahaya merokok.Metode: Studi Cross sectional dilakukan pada siswa 69 kelas X di 2 SMA Wilayah Kota Depok yang dipilih secara total sampling. Variabel penelitian berupa media promosi kesehatan, poster dan video terhadap kesadaran bahaya merokok.Data primer diambil secara langsung menggunakan kuesioner baku yang telah diuji validitas dan reabilitasnya. Data diuji menggunakan uji Wilcoxon.Hasil: Didapatkan perbedaan yang signifikan antara poster promosi kesehatan penurunan sebanyak 9 orang dan peningkatan sebanyak 12 orang. Perbedaan ini tidak signifikan (p >0,05) dengan nilai p 0,972. Tindakan pencegahan kesehatan berbasis poster tidak berpengaruh terhadap pengetahuan merokok. Media video promosi kesehatan memiliki p-value 0,000 (p <0,05) dengan penurunan sebanyak 2 orang dan peningkatan sebanyak 24 orang.Kesimpulan: Penggunaan media promosi kesehatan video dan media poster meningkatkan pemahaman remaja tentang bahaya merokok. Media video lebih efektif daripada poster dalam memberikan informasi kepada siswa SMA di Depok. Saran untuk pemerintah adalah menggunakan video promosi kesehatan sebagai strategi inovatif untuk mencegah remaja merokok. Media promosi kesehatan harus dibagikan di platform media sosial popular yang sering digunakan oleh para siswa seperti YouTube, Instagram, dan TikTok.Kata Kunci: Media, Merokok, Poster, Promosi Kesehatan, Video